Engaging Patient and Family Advisors in Health-Care System Planning: Experiences and Recommendations. (June 2020) - Wheeler, Sarah; MacKay, Jenna; Moody, Lesley; D'Souza, Junell; Gilbert, Julie
Background: Patient and family advisors (PFAs) contributed to the development of the Ontario Cancer Plan IV (OCP IV), a 4-year strategic plan for Ontario, Canada's cancer system produced by Cancer Care Ontario. Objective: To understand the barriers and facilitators PFAs experience when they are engaged in health-care system planning and provide recommendations for future engagement. Method: Patient and family advisors who had an ongoing involvement in the development of the OCP IV were invited to take part in an interview. Qualitative data were analyzed for emergent themes and recommendations were generated. Results: Key emergent themes highlighted necessary elements for effective engagement of PFAs. These included rapport (feeling valued, included as an equal and having supportive interpersonal relationships), communication (clarity and transparency, shared language and understanding, feeling heard, and effective teleconferencing), and leadership (from PFAs and staff). Recommendations for optimizing PFA engagement in health-care system planning were generated. Conclusion: Patient and family advisors can be effectively engaged in system-level strategic planning by building reciprocal rapport, effective communication, and strong leadership. Notably, developing "systems literacy" in PFAs is key to ensuring the voices of patients and their families are heard and reflected in health-care system plans.